2022
DOI: 10.3390/su14159537
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Critical Success Factors for BIM Implementation in Developing Countries: Sampling the Turkish AEC Industry

Abstract: One of the latest advancements transforming the global architectural, engineering, and construction (AEC) industry is building information modeling (BIM). Although BIM implementation is at high level in developed countries, it is at a lower level in developing countries. BIM is new to the construction industry in Turkey, with only minor construction firms having implemented it. When making projections based on the current state of the Turkish AEC industry, it is foreseen that it will become mandatory in the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…In the context of these observations, the conclusions drawn from the article are as follows: BIM has the potential to transform the AEC industries, bringing benefits to both investors and contractors. However, to fully utilize them, further training and education in BIM are necessary, as well as the introduction of appropriate legal regulations and the implementation of BIM procedures in construction companies [73]. It is worth mentioning that to fully and correctly implement this methodology and benefit from it, one should strictly base it on the standards from the ISO 19650 series [74].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of these observations, the conclusions drawn from the article are as follows: BIM has the potential to transform the AEC industries, bringing benefits to both investors and contractors. However, to fully utilize them, further training and education in BIM are necessary, as well as the introduction of appropriate legal regulations and the implementation of BIM procedures in construction companies [73]. It is worth mentioning that to fully and correctly implement this methodology and benefit from it, one should strictly base it on the standards from the ISO 19650 series [74].…”
Section: Discussionmentioning
confidence: 99%
“…Although it has multifaceted advantages such as simplicity and flexibility (da Cruz et al, 2022), the AHP can only consider a limited number of criteria and alternatives (Tan et al, 2022). The AHP has relatively stringent requirements for independence among criteria, and its results are heavily conditioned on pairwise comparisons (Jalilzadehazhari et al, 2019).…”
Section: Mcdm Methodsmentioning
confidence: 99%
“…Although BIM methodology is a well-covered research topic, several studies have been conducted from different perspectives, highlighting the benefits of BIM implementation by some authors (Tan et al, 2022), where productivity and efficiency improvement are emphasized. Another view of these works relates to adopting CSFs for different BIM perspectives (Al-Ashmori et al, 2022).…”
Section: Differences In Csfs and Benefitsmentioning
confidence: 99%
“…In the published literature, the integration of LC, BIM, and FM has been realized in various domains depending on contextual, organizational, and cross-organizational factors. It has been observed that integrated applications of LC, BIM, and FM include a variety of combinations of LC, BIM, and FM [86][87][88][89]. Variants in the implementation include BIM-enabled FM, i.e., BIM-FM, LC, and FM, i.e., LC-FM, and integrated applications of LC, BIM, and FM, i.e., LC-BIM-FM [48,71,72,76].…”
Section: Combinations Of Lc Bim Fmmentioning
confidence: 99%
“…In addition, many organizations and national economies have reported benefits associated with integrating LC, BIM, and FM [62][63][64]. These integrated applications include an assorted variety of combinations of LC, BIM, and FM [48,[62][63][64]71,72,76,[86][87][88][89], albeit a prominent challenge in developing countries is how to identify the right combinations for integrating LC, BIM, and FM. Since FM and LC can be regarded as tools used during the implementation of a constructed facility, BIM can be used to capture data and information relevant to FM and LC throughout the life cycle of a construction project, for example, a large building.…”
Section: Combinations Of Lc Bim Fmmentioning
confidence: 99%